Smart Digital Content Marketing, Strategi Membidik Konsumen Millennial Indonesia - Rina Suthia Hayu (Universitas Islam Kadiri, 2019)
Millennials in Indonesia currently have the largest market share, but there are not many studies that discuss marketing in millennials in Indonesia, especially marketing in business units that market their products to end consumers (B2C-business to consumer). Judging from the current phenomenon, namely 1) The rise of growth and competition from both foreign and local online retailers competing in Indonesia. 2) Increasingly developing software and hardware technology in digital marketing which gave birth to marketing innovations. 3) Large millennial role in digital marketing, because now they are a generation that understands technology, grows in the world of social media, grew up in a culture of expression, is aware of the attachment to technological change and able to learn through online interaction, has encouraged researchers to research conceptual by creating renewal in the variable attributes of Digital Content Marketing. This study uses observations of phenomena and literature review of previous research so as to produce a new formula namely Smart Digital Content Marketing that is comprehensive based on the suitability of the characteristics of the Indonesian millennials. This study is expected to benefit Indonesian online businesses and provide opportunities for future researchers to conduct surveys and statistical tests.